2009
DOI: 10.1097/tp.0b013e3181a5e9f8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Change in the United Kingdom Pediatric Donor Organ Allocation Policy for Intestinal Transplantation

Abstract: The new prioritization of the national pediatric donor allocation favoring IT has resulted in an increased number of procedures, without an impact on waiting list mortality for small children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In the post-1998 era, of the 230 children assessed for ITx 98 were recommended for transplant, 45 intestinal transplants were performed (7 IITx transplant and 14 size-matched CLITx, 23 CRLITx; 13 children also had reduction in donor intestinal length ), whereas 24 children died on the waiting list. Although the number of intestinal transplants increased during the timeperiod, the lack of availability of small sized donors in UK resulted in increased deaths on transplant waiting list in children under 10 kg [7].…”
Section: Impact Of Using Crlitx On Number Of Transplants and Death Onmentioning
confidence: 99%
“…In the post-1998 era, of the 230 children assessed for ITx 98 were recommended for transplant, 45 intestinal transplants were performed (7 IITx transplant and 14 size-matched CLITx, 23 CRLITx; 13 children also had reduction in donor intestinal length ), whereas 24 children died on the waiting list. Although the number of intestinal transplants increased during the timeperiod, the lack of availability of small sized donors in UK resulted in increased deaths on transplant waiting list in children under 10 kg [7].…”
Section: Impact Of Using Crlitx On Number Of Transplants and Death Onmentioning
confidence: 99%
“…As in adult medicine, the number of children who would benefit from organ transplantation far exceeds the number of donors 1 2. While seat belts, cycle helmets and improvements in paediatric intensive care have led to a decrease in the number of children dying from severe traumatic brain injury,3 there can be little doubt that opportunities for donation are missed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Number of deaths per 1000 patient years waiting for a transplant. (17,18). We observed that the 23 extra points allotted to pediatric liver-intestine candidates in period 4 decreased their mortality substantially and narrowed the gap between liver-intestine and liver-only mortality (Figure 2).…”
Section: Discussionmentioning
confidence: 84%